2022
DOI: 10.1007/s10753-021-01543-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of NCR− Type 3 Innate Lymphoid Cells and Their Role in Mice with Bronchopulmonary Dysplasia

Abstract: Abstract—Inflammation is one of the important pathogenesis of bronchopulmonary dysplasia (BPD). Type 3 innate lymphoid cells (ILC3) play a role in a variety of inflammatory lung diseases. In this study, we established the BPD model by injecting lipopolysaccharide into the amniotic cavity of pregnant mice. Here, we investigated the dynamic changes of ILC3 and NKP46− ILC3 population in lung tissues of mice from BPD and the control groups. Results showed that the proportion of ILC3 and NKP46−ILC3 in the BPD group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…IL-17 plays an important role in instigating and/or exacerbating fetal inflammatory responses that increase neonatal morbidities and mortalities associated with sepsis and BPD 26 . In experimental BPD, IL-17 was shown to be secreted by type 3 innate lymphoid cells, and it can aggravate lung inflammation 27 . High TNF-α levels were detected in preterm infants with BPD 28 and neonatal mice with experimental BPD 29 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 plays an important role in instigating and/or exacerbating fetal inflammatory responses that increase neonatal morbidities and mortalities associated with sepsis and BPD 26 . In experimental BPD, IL-17 was shown to be secreted by type 3 innate lymphoid cells, and it can aggravate lung inflammation 27 . High TNF-α levels were detected in preterm infants with BPD 28 and neonatal mice with experimental BPD 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that IL-17 A level is significantly upregulated and the IL-17 signaling pathway is significantly activated in the external circulation of children with BPD [ 10 , 34 , 35 ]. In the BPD mouse model, the expression of Th17 cells was enhanced in lung, demonstrating strong pro-inflammatory properties and resistance to Treg mediated inhibition [ 13 , 37 , 38 ]. During the critical developmental window of premature infants, the Th17 biased pro-inflammatory response caused by intrauterine inflammation weakens the immune program, leading to “dysfunctional immune activation“[ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was accompanied by an increase in the IL-6 concentration in neonatal tracheal aspirates, which was linked to the progression of BPD [ 11 , 12 ]. Our previous studies found that that lung inflammation was significantly reduced in BPD mice after the administration of anti-IL-17 neutralizing antibody [ 13 ]. Therefore, we concluded that IL-17 and the Th17 cell response play an important role in BPD development.…”
Section: Introductionmentioning
confidence: 99%